Memória, infância e brincar em escritos de Walter Benjamin: cultura lúdica e processos de formação e prática docente - Alves, Cláudia Ximenez [UNESP]; Silva, Marilda da [UNESP]; Oliveira, Paula Ramos de [UNESP] (My University, 2011)
This text aims to present some ideas of the philosopher Walter Benjamin, one of the most intriguing intellectuals of our time, trying to outline in his work the relationship that the author establishes between childhood playing and ludic culture, more precisely regarding the memory of playing, childhood, culture, history and memory in contemporary society after the twentieth century. Thus, in order to identify reinterpreted experiments, as places, forms of playing and types of toys made out of this paradigm, we were guided by the notes, essays, translations and articles in which Benjamin identified conceptions of childhood and ludic culture. Benjamin's view of childhood is not childish, simplistic or reductive. His works allow us to discuss and justify the need for a more detailed analysis on the phenomenon of development and teaching practice within the everyday schoolchildren. By revisiting the original ideas, and irreverent criticism of Benjamin, thinking education from his account, we hope to contribute with other studies in the field of education, by elucidating the process of development and teaching practice in relation to the ludic childhood culture, specifically regarding childhood and the places of childhood in the contemporary context.

Este texto tem como objetivo apresentar reflexões do pensador Walter Benjamin, um dos mais instigantes intelectuais da modernidade, buscando caracterizar por intermédio da leitura de seus escritos a relação que o autor estabelece entre brincar na infância e cultura lúdica, mais precisamente sobre a memória do brincar e as relações existentes entre infância, cultura, história e memória na sociedade contemporânea pós século XX. Para tanto, nos pautamos em notas, ensaios, traduções e artigos de Benjamin nos quais identificamos concepções de infância e cultura lúdica representadas em experiências vividas em espaços, formas de brincar e tipos de brinquedos constituídos por (e constituintes de) seu paradigma. Observamos no pensamento benjaminiano uma visão de infância não infantilizada, não simplista e não reducionista. Suas obras permitem-nos discutir e justificam a necessidade de uma análise mais apurada sobre o fenômeno da formação e da prática docente no interior do cotidiano infantil escolar. Ao revisitar as idéias originais, críticas e irreverentes de Benjamin, pensando a Educação com e a partir dele, espera-se contribuir com outros estudos que, no campo da educação, vêm elucidando perspectivas acerca do processo de formação e prática docente em relação à cultura lúdica infantil, mais precisamente acerca da infância e dos lugares da infância no contexto contemporâneo.
Memory, childhood and playing in the writings of Walter Benjamin: ludic culture, process of development and teaching practice
Keywords: Childhood; Ludic memory; Playing; Infância; Memória lúdica; Brincar